EMERGENCY MANAGEMENT OF THE PRE-HOSPITAL PHASE IN COVID 19 PATIENT: LITERATURE REVIEW - M Sobirin Mohtar; Mahmuddin Rahma (Poltekkes Kemenkes Semarang, 2021)
The addition of Covid-19 cases took place quite quickly and has spread between countries. The high incidence is important to improve health services, especially the pre-hospital phase services. In this phase, good emergency management will reduce the number of disability to death by up to 50% by starting from activating calls prior to the incident location, health workers who understand first aid and transportation using an ambulance and being observed until they arrive at the hospital. Knowing the Pre-Hospital Phase Emergency Management in Covid-19 Patient: Literature Review. The research method used is a literature review. In this method, online searches for articles, journals and books are carried out using accessible databases, namely Google Scholar, PubMed, and Biomed Central. It is known from 10 Literature Articles, journals and books in the emergency management of Covid-19 in the Pre-Hospital phase must be done as much as possible to minimize the number of deaths and transmission that occurs. Handling of emergency Covid-19 in the Pre-Hospital phase includes: Basic and Advanced Life Support (BLS), Oxygen Therapy, Personal Protective Equipment (PPE), and Patient Transport. It is important for medical personnel to pay attention to many things in providing emergency nursing care to Covid-19 patient. Pre-Hospital emergency measures for patient with Covid-19 can be carried out in various ways to improve the patient condition while at the Pre-Hospital, besides that, it can also prevent transmission to medical personnel and people around Covid-19 patient.